1990
DOI: 10.1007/bf02540508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moisture, microwave heating, and live steam treatment on phospholipase D activity in soybeans and soy flakes

Abstract: The impact of enzyme activity on the nonhydratable phospholipid content of crude soybean oil has been evaluated. A radiochemical method was used to assay phospholipase D activity in whole and flaked soybeans stored under a variety of storage and enzyme inactivating conditions. The crude enzyme was isolated and incubated with a mixture of 14C-labeled and unlabeled phosphatidylcholine. The amount of liberated radioactive choline was used as a measure of enzyme activity. Whole soybeans with moisture contents of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…The phospholipase D was extracted from milled soybeans (List et al 1990(List et al ,1992 by a modification of the method proposed by Nakayama et al (1981). Methodological steps were established as follows:…”
Section: Plda Determined By the Extraction Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The phospholipase D was extracted from milled soybeans (List et al 1990(List et al ,1992 by a modification of the method proposed by Nakayama et al (1981). Methodological steps were established as follows:…”
Section: Plda Determined By the Extraction Methodsmentioning
confidence: 99%
“…Discrepancies in the values of PLD activity (PLDA) arise from comparing the results obtained by List et al (1990List et al ( , 1992 and by Tosi et al (1999). The PLDA found by Tosi et al was 150 times the PLDA found by List et al In their works, List et al (1990, 1992 applied the method of extracting the enzyme from the soybean original matrix according to a modification of the method proposed by Nakayama et al (1981) to extract the PLD from white cabbage.…”
Section: Soybean Phospholipase D Activity Determination a Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…However, owing to its efficient heat transfer, which allows rapid heating, there is increasing interest in heating via electromagnetic radiation, such as microwave and infrared. Several authors studied the effect of microwave heating and found decreased phospholipase D activity in soy meal [2], decreased myrosinase activity in rapeseed [3], and inactivation of lipase and lipoxygenase [4,5]. We extensively studied the use of microwave heating for the heating of rape and sunflower seeds and evaluated its effect on the resulting oil quality.…”
Section: Hitzevorbehandlung Vonmentioning
confidence: 99%
“…NHP content in CO increases at the same time as the extraction temperature (4). List et al (3,5) proved that moisture, cellular disruption, heat, and PLD activity are factors that promote NHP formation; PLD inactivation minimizes it. PLD was fully inactivated in whole soybeans by a 8-9 min microwave treatment at 115-120°C, and by a live steam treatment at about 110°C of soyflakes.…”
mentioning
confidence: 99%